Opening up Bodyspace: Perspectives from Posthuman and Feminist Theory - Xenia Kokoula (Footprint)
A rethinking of space, a rethinking of the body and a rethinking of a design processes involving both are long overdue within space-related disciplines. Over the last decades, architectural discourse has been invigorated by opening up container conceptions of space, by exploring a new dynamic understanding of space and focusing on its production processes. But a systematic, theoretically-informed understanding of the body along the same terms has yet to be achieved. Such a search for new visions and concepts of corporealities can start at different places. This essay attempts a cross-disciplinary, speculative foray into the terrain of posthuman, nonhuman and feminist theory. From this diverse body of scholarship it is possible to develop theses for open, permeable and inextricably entangled bodies inhabiting an equally dynamic space. These theses are examined not only within their own disciplinary discourses but also as aesthetic categories and spatial organisation principles aimed at tentatively exploring the implications for space-related disciplines including architecture and design.